TAX RISK MANAGEMENT AND FINANCIAL REPORTING QUALITY - Arfandi Arfandi; Amiruddin Amiruddin; Rahmawati HS (CV. Adiba Aisha Amira, 2026)
This study aims to comprehensively examine the relationship between tax risk management and financial reporting quality through a literature review approach. In a global context characterized by increasing complexity of tax regulations and demands for transparency of financial information, tax risk management has become a strategic aspect that not only influences fiscal compliance but also impacts the integrity and credibility of corporate financial reports. The method used in this study is a systematic literature review, which categorizes, compares, and synthesizes the results of previous research from various reputable scientific journals. The results indicate that effective tax risk management tends to improve financial reporting quality by reducing fiscal uncertainty, minimizing profit manipulation practices, and strengthening a company's internal oversight mechanisms. Conversely, weak tax risk management has the potential to reduce financial reporting quality due to increased tax aggressiveness and the risk of reporting errors. This study confirms that tax risk management functions not only as a tax compliance tool but also as a crucial instrument in improving the quality of corporate financial information. This study is expected to serve as a reference for further research and as a consideration for regulators and practitioners in strengthening tax governance and financial reporting.